Wanted: Change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Moving targets: towards monitoring rural decentralisation By F van Oosterhout, Bulletin 349, KIT Press, 2002. 50 pp. ISBN 90 6832 838 7 Euro 11.50